Improving the Nutritional Resource Environment for Healthy Living Through Community-based Participatory Research - Sloane, David C (Blackwell Science Inc, 2003)
OBJECTIVES: To build health promotion capacity among community residents through a community-based participatory model, and to apply this model to study the nutritional environment of an urban area to better understand the role of such resources in residents' efforts to live a healthy life. DESIGN: A multiphase collaborative study that inventoried selected markets in targeted areas of high African-American concentration in comparison with markets in a contrasting wealthier area with fewer African Americans. SETTING: A community study set in the Los Angeles metropolitan area. PARTICIPANTS: African-American community organizations and community residents in the target areas. INTERVENTIONS: Two surveys of market inventories were conducted. The first was a single-sheet form profiling store conditions and the availability of a small selection of healthy foods. The second provided detailed information on whether the store offered fruit, vegetables, low-fat dairy products, dried goods and other items necessary for residents to consume a nutritious diet. RESULTS: The targeted areas were significantly less likely to have important items for living a healthier life. The variety and quality of fresh fruit and vegetable produce was significantly lower in the target areas. Such products as 1% milk, skim milk, low-fat and nonfat cheese, soy milk, tofu, whole grain pasta and breads, and low-fat meat and poultry items were sig-nificantly less available. CONCLUSIONS: Healthy food products were significantly less available in the target areas. The authors conclude from these results that the health disparities experienced by African-American communities have origins that extend beyond the health delivery system and individual behaviors inasmuch as adherence to the healthy lifestyle associated with low chronic disease risk is more difficult in resource-poor neighborhoods than in resource-rich ones.